The Form of Slang Terms in the “Kingsman: the Golden Circle” Movie - Julio Agsa; Ambalegin Ambalegin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aimed to analyze the slang terms found in the Kingsman: The Golden Circle (2015) movie. This descriptive qualitative research focused on slang formation in this movie. This research used Bloomfield and Guth’s theories. The source of the data was all slang terms in the movie. Method of collecting data used observational method with non-participatory technique. In analyzing the data, this research used referential identity method with competence in equalizing technique. From this research, the results showed that there were 1 slang term in abbreviation such as teeth, 14 slang terms in shortened form such as wanna, i’ll, i’ve, they’re, d’d, thinkin’, doin', hookin' up, ain’t, y’all, gent, 'em, ma'am, meth, champ, shittin’, 8 slang terms in interjection such as fuck, fucking hell, shit, cheers, yep, bloody hell, crap, fuck off, 3 slang terms in figurative expressions such as bullshit, kick in, dumbass and 12 slang terms in nickname such as buddy, babe, bruv, nan, fellas, pal, boy, mate, love, kid, folks, sugar. Based on the results, it can be concluded that the most widely used slang type is shortened form and the least used is abbreviation. Keywords: Slang Formation, Movie, Slang Terms